RETRACTED: Design of environmental striped fabrics based on the assortment of possibilities of weaving machines - Doniyorova Matluba; Doniyorov Bektosh; Shamiyev Diyor; Sadikova Gulbahor (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001